Makna Popularitas dalam Lirik Lagu “The Lucky One” Karya Taylor Swift: Sebuah Analisis Semiotika - Qilan Umara Ridwan (Fakultas Ilmu Komunikasi Universitas Pancasila, 2018)
This study aims to find the meaning of the signifier and the signified, syntagmatic and the relationship of signification of the song lyrics. The method used is qualitative with an interpretive semiotic analysis approach or constructivism. The conclusion from the results found is, there are various meanings of popularity based on the sentences analyzed namely, fame, luxury, publication, wealth, optimistic feelings, beautiful and cool, worshiped, considered lucky but in the end feelings change, feel used, can be replaced, confused, lonely and unlucky. Suggestions for further research to explore deeper synchronous and chronic parts of the language used in the song.